Clinical behavior of Dengue in Cúa infants. Miranda State. Venezuela 2014 - Alexander Torres Molina; Osvaldo Urrutia Mora; Norge Cabreja Silot; Adolfina Martínez Martínez; Yamila Navarro Caboverde (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: In tropical south-american areas, dengue has increased sharply its incidence and morbidity rate, mainly in the infant population. Venezuela is among the countries with higher epidemiological effects. Objective: to describe the clinical behaviour of dengue in children assisted in the Hospital Dr. Osio, in Cúa, Miranda. Methods: cross study realized from July to December 2014, which analyzed the variables of, severity main clinical manifestations, alarm signs in 284 children with the diagnosis of dengue. The results were expressed through an absolute average frequency, standard deviation and percentage. Results: children between 10-13 years old prevailed (37,68 %) and children aged between 5-9 (31,69 %). In the 82,40 % of cases the disease showed signs of alarm, 13,73 with signs of alarm and 3.87 % presented severe dengue. The abrupt decrease in platelets was observed in 63,64 % of the patients with severe dengue. Conclusion: even though the disease presented generally with signs of alarm, sharp decrease of platelets, mucosal bleeding, and hematocrit increase were the most commonly observed. Plasma extravasation and severe deterioration of target organs were the main conditions of vital compromise.